1983
DOI: 10.1002/j.1460-2075.1983.tb01625.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of transformation by Rous sarcoma virus on the amount, phosphorylation and enzyme kinetic properties of enolase.

Abstract: Using chicken embryo fibroblasts infected with the NY68 transformation‐defective temperature‐sensitive mutant of Rous sarcoma virus, the phosphorylation and enzyme kinetic properties of enolase have been studied before, and at different stages after, the onset of transformation. A method for purification of enolase was developed, which minimized dephosphorylation. Two enolase (EC 4.2.1.11) isoenzymes were separated by isoelectric focussing revealing that it was the gammagamma form (pI 5.2‐6.7) which had become… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1983
1983
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 44 publications
(27 reference statements)
0
15
0
Order By: Relevance
“…It has been reported that enolases from various sources can be phosphorylated, and that phosphorylation reduces catalytic activity (5). Alternatively, phosphorylation could be a signal for proteolysis (10).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that enolases from various sources can be phosphorylated, and that phosphorylation reduces catalytic activity (5). Alternatively, phosphorylation could be a signal for proteolysis (10).…”
Section: Resultsmentioning
confidence: 99%
“…Low mol wt compounds were removed by centrifugation of samples of clarified homogenates through 2.5-mL bed volume columns of Sephadex G-25, previously equilibrated with homogenization buffer, set in conical Corex tubes. Enzyme assays, separation of the enolase isozymes, immunochemical analyses, and all other materials and methods have been previously described (1 [1][2][3][4][5][6][7][8][9][10][11][12][13]. The data for total endosperm enolase activity were analyzed using the curve-fitting capability of the Sigmaplot 3.0 graphics program from Jandel Scientific.…”
mentioning
confidence: 99%
“…Also, enolase has been shown to be a substrate for phosphorylation by epidermal growth factor-receptor kinase (Reiss et al, 1986) and protein kinase C (Nettelblad and Engstrom, 1987) in mammalian systems, by a Ser/Thr/Tyr kinase in yeast (Stern et al, 1991) and in Escherichiu coli (Dannelly et al, 1989). Furthermore, alterations in activity based on changes in phosphorylation state provide compelling evidence for the posttranslational regulation of enolase (Eigenbrodt et al, 1983;Nettelblad and Engstrom, 1987). Further investigations are needed to elucidate the phosphorylation status of enolase in M .…”
Section: Discussionmentioning
confidence: 99%
“…The kinase reactions were performed by incubating immunoprecipitated beads with 20 l of kinase buffer supplemented with 20 M ATP and 3 Ci of [␥- 32 P]ATP at 30°C for 30 min. To assess the IKK␣␤ and c-Src activities, 0.5 g of GST-IB␣ protein (aa 1-317) and 1 g of acetic acid-denatured enolase (40,41) were respectively added as the substrates. The reaction mixtures were analyzed by 12% SDS-PAGE followed by autoradiography.…”
Section: Immunoprecipitation and Protein Kinase Assaysmentioning
confidence: 99%